Genetic studies of multiple consanguineous Pakistani families segregating oculocutaneous albinism identified novel and reported mutations. (13th March 2019) - Gul, Hadia; Shah, Abdul Haleem; Harripaul, Ricardo; Mikhailov, Anna; Prajapati, Kamalben; Khan, Ejazullah; Ullah, Farman; Zubair, Muhammad; Ali, Muhammad Zeeshan; Shah, Ayesha Haleem; Salman, Said; Khan, Saadullah; et al.
Abstract: Oculocutaneous albinism (OCA) is an autosomal‐recessive disorder of a defective melanin pathway. The condition is characterized by hypopigmentation of hair, dermis, and ocular tissue. Genetic studies have reported seven nonsyndromic OCA genes, among which Pakistani OCA families mostly segregate TYR and OCA2 gene mutations. Here in the present study, we investigate the genetic factors of eight consanguineous OCA families from Pakistan. Genetic analysis was performed through single‐nucleotide polymorphism (SNP) genotyping (for homozygosity mapping), whole exome sequencing (for mutation identification), Sanger sequencing (for validation and segregation analysis), and quantitative PCR (qPCR) (for copy number variant [CNV] validation). Genetic mapping in one family identified a novel homozygous deletion mutation of the entire TYRP1 gene, and a novel deletion of exon 19 in the OCA2 gene in two apparently unrelated families. In three further families, we identified homozygous mutations in TYR (NM_000372.4:c.1424G > A; p.Trp475*), NM_000372.4:c.895C > T; p.Arg299Cys), and SLC45A2 (NM_016180:c.1532C > T; p.Ala511Val). For the remaining two families, G and H, compound heterozygous TYR variants NM_000372.4:c.1037‐7T > A, NM_000372.4:c.1255G > A (p.Gly419Arg), and NM_000372.4:c.1255G > A (p.Gly419Arg) and novel variant NM_000372.4:c.248T > G; (p.Val83Gly), respectively, were found. Our study further extends the evidence of TYR and OCA2 as genetic mutation hot spots in Pakistani families. Genetic screening of additional OCA cases may also contribute toward the development of Pakistani specific molecular diagnostic tests, genetic counseling, and personalized healthcare.